2023
DOI: 10.3847/1538-4357/acd180
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Disk Instability Model to All Quasiperiodic Eruptions

Abstract: After the first quasiperiodic eruption (QPE; GSN 069) was reported in 2019, four other sources have been identified as a QPE or a candidate. However, the physics behind QPEs is still unclear, although several models have been proposed. Pan et al. proposed an instability model for an accretion disk with magnetically driven outflows in the first QPE of GSN 069, which is able to reproduce both the light curve and the evolution of the spectra fairly well. In this work, we extend this model to all QPEs. We improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…This temperature fluctuation bears resemblance to the disk instability scenario. Particularly, we noticed that the disk instability model has been proposed to explain QPEs in previous studies (Pan et al 2023;Śniegowska et al 2023) and the X-ray flares observed in ASASSN-14ko are rather similar to QPEs. Another popular model involved in explaining QPE is the star-disk collision model (Xian et al 2021;Linial & Metzger 2023), which is yet disfavored by a lower energy released by 1 order of magnitude than that observed in individual flares of ASASSN-14ko (∼10 50 erg).…”
Section: Other Scenariossupporting
confidence: 64%
“…This temperature fluctuation bears resemblance to the disk instability scenario. Particularly, we noticed that the disk instability model has been proposed to explain QPEs in previous studies (Pan et al 2023;Śniegowska et al 2023) and the X-ray flares observed in ASASSN-14ko are rather similar to QPEs. Another popular model involved in explaining QPE is the star-disk collision model (Xian et al 2021;Linial & Metzger 2023), which is yet disfavored by a lower energy released by 1 order of magnitude than that observed in individual flares of ASASSN-14ko (∼10 50 erg).…”
Section: Other Scenariossupporting
confidence: 64%
“…There are a large number of models proposed to explain the origin of QPEs, fitting broadly into two categories. The first class is recurring limit cycle instabilities within the SMBH accretion disk (Raj & Nixon 2021; Pan et al 2022;Śniegowska et al 2023;Kaur et al 2023;Pan et al 2023), inspired by observations of recurring high-amplitude outbursts (the heartbeat states) seen in black hole X-ray binaries GRS 1915+105 (Belloni et al 2000) and IGR J17091-3624 (Altamirano et al 2011). In fact, Wang et al 2024 reported high-amplitude variability at 0.5 Hz, which scaled to a 10 5 M e SMBH corresponding to ∼2 days, similar to the QPE timescales.…”
Section: Qpe Modelsmentioning
confidence: 99%
“…Currently, the origin of QPEs is still debated. Existing models are separated broadly into (a) recurring limit cycle instabilities within the SMBH accretion disk (Raj & Nixon 2021; Pan et al 2022;Śniegowska et al 2023;Kaur et al 2023;Pan et al 2023), or (b) the interaction of the SMBH with a lower-mass orbiting companion, which allows many different prescriptions for precisely how the X-ray emission is Original content from this work may be used under the terms of the Creative Commons Attribution 4.0 licence. Any further distribution of this work must maintain attribution to the author(s) and the title of the work, journal citation and DOI.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, QPEs have also been suggested to be caused by instabilities in large AGN-like disks (e.g., Sniegowska et al 2020;Raj & Nixon 2021;Pan et al 2023). On one hand, it seems less likely that the connection between QPEs and TDEs is intrinsic in this case.…”
Section: Accretion Disk Instability Scenariomentioning
confidence: 99%
“…Their timing and spectral properties, including quasi-periodic behavior and the emergence of an additional hot thermal component during the outburst rise, are unique among the known variability of active galactic nuclei (AGNs; Miniutti et al 2019;Giustini et al 2020;Arcodia et al 2021). QPEs may relate to accretion disk instabilities (Sniegowska et al 2020;Raj & Nixon 2021;Pan et al 2023) or to the interaction between the supermassive black hole (SMBH; or an accretion disk surrounding it) and a stellar-mass companion. The latter class of models comes in many flavors, including repeated partial tidal disruptions (King 2022), Roche lobe overflow (Krolik & Linial 2022;Metzger et al 2022;Lu & Quataert 2023), and star-disk or BH-disk interactions (Franchini et al 2023;Linial & Metzger 2023;Tagawa & Haiman 2023;Zhou et al 2024).…”
Section: Introductionmentioning
confidence: 99%